The Autonomic Nervous System in Neonatal Infants at Surgery - V. A. Mikhelson; A. D. Sepbayeva; Ye. Yu. Bersenev; Yu. V. Zhirkova; N. G. Ilyina (Общая реаниматология, 2010)
Objective: to evaluate the neonatal autonomic nervous system, by analyzing cardiac rhythm variability (CRV). Subjects and methods: Examinations were made in 7 full-term neonates with the physiological course of the early adaptation period on days 2 and 5 after birth (a control group) and in 11 neonatal babies with various surgical pathology during surgical interventions (a study group). Results. Just in the preoperative period, the neonatal infants with surgical pathology showed a comparatively higher activity of the sympathetic nervous system than did the healthy infants, which determines the intensive performance of most systems of the body. The anesthesia introduction period and tracheal intubation were accompanied by a predominance of very low frequency (VLF) fluctuations associated with energy metabolic regulation. A drastic increase in stress index by almost 2 times and a reduction in spectrum power are indicative of the considerable tension of regulatory systems. The basic stage is characterized by a preponderance of high-frequency (HF) fluctuations and an increase in VLF ones by the end of surgery with lower low-frequency (LF) power fluctuations and by the maximum SI values, which indicates the enhanced activity of the subcortical autonomic centers in the hypothalamo-pituitary system and cerebral cortex. Conclusion. The CRV indicators recorded at all surgical stages in neonatal babies with surgical pathology reflect a critical increase in the activity of autonomic cardiovascular system regulation, which are undetectable by conventional anesthesiological monitoring techniques, in which the changes in hemodynamics (blood pressure and heart rate) were characterized by the relative stability of the indicators. The studies supported the informative value of – using the methods for statistical and spectral analyses of CRV in neonates at surgery to optimize anesthesiological defense and to make a timely correction of impaired homeostasis.